TINJAUAN SISTEM PENGERING SILIKA GEL BERBASIS ABU SEKAM PADI MENGGUNAKAN SISTEM VAKUM TRAY DRYER TERHADAP KEMAMPUAN DAYA SERAP - Arisqi, Muhamad Muammar; Junaidi, Robert; Fadarina (Politeknik Negeri Sriwijaya, 2021)
Rice husks are waste from the agricultural industry. Usually this rice husk waste is burned and thrown away without any further processing so that it can pollute the environment. To reduce waste from rice husk ash, in this study rice husk ash will be used as an adsorbent in increasing the adsorbent capacity of silica gel. Rice Husk Ash contains 97.3% Silica. The high silica content of Rice Husk Ash has the potential to be used as a material for making silica-based materials such as silica gel. The large amount of silica (SiO2) contained in rice husk ash makes rice husk ash potential as a raw material for making silica gel. Rice husk ash as adsorbent can also absorb dye from woven fabric waste which is directly disposed of into receiving waters. In this research phase, starting from the extraction process of rice husk ash with 2M KOH at a temperature of 110 oC for 2 hours. Furthermore, it will be lightened in a desiccator and filtered to get a filtrate in the form of Na2SiO3. The filtrate will be mixed with H2SO4 solution until the pH is at a value of 7 and dry it in an oven with a variation of 4, 5 and 6 hours at a temperature of 120 oC. To see the silica gel content using Gravimetry, while to analyze the absorption of dyes in woven fabric waste using UV-Vis Spectrophotometry.